2013
DOI: 10.1186/1743-8977-10-18
|View full text |Cite
|
Sign up to set email alerts
|

Effects of airborne pollutants on mitochondrial DNA Methylation

Abstract: BackgroundMitochondria have small mitochondrial DNA (mtDNA) molecules independent from the nuclear DNA, a separate epigenetic machinery that generates mtDNA methylation, and are primary sources of oxidative-stress generation in response to exogenous environments. However, no study has yet investigated whether mitochondrial DNA methylation is sensitive to pro-oxidant environmental exposures.MethodsWe sampled 40 male participants (20 high-, 20 low-exposure) from each of three studies on airborne pollutants, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
140
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(146 citation statements)
references
References 37 publications
(46 reference statements)
2
140
2
2
Order By: Relevance
“…Our group previously reported that blood platelet mtDNA methylation levels are higher in CVD patients compared with healthy persons 12. Possibly because of the use of a single blood cell type (platelets), the observed differences in mtDNA methylation between CVD patients and healthy persons were relatively larger (20%) than other studies that have used mixed cell–type populations, such as buffy coat 25.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Our group previously reported that blood platelet mtDNA methylation levels are higher in CVD patients compared with healthy persons 12. Possibly because of the use of a single blood cell type (platelets), the observed differences in mtDNA methylation between CVD patients and healthy persons were relatively larger (20%) than other studies that have used mixed cell–type populations, such as buffy coat 25.…”
Section: Discussionmentioning
confidence: 73%
“…Next, 1 µL of converted DNA was used for polymerase chain reaction (PCR) amplification using GoTaq Hot Start polymerase (Promega). PCR conditions and primer sequences for mitochondrial assays have been described previously 12. Pyrosequencing was performed using the PSQ Q96 MD pyrosequencing system (Qiagen), as described previously.…”
Section: Methodsmentioning
confidence: 99%
“…Alterations in mitochondrial DNA methylation have been demonstrated in cardiovascular disease 51 and in response to environmental exposures. 52,53 It has been speculated that such epigenetic changes may give rise to the altered mitochondrial function observed in drug addiction. 14 However, our study did not identify differential methylation of mitochondrial genes in response to morphine induction.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, researchers are finding it worthy to investigate potential links between PM 2.5 exposure and adverse birth outcomes (Slama et al, 2008;Dadvand et al, 2013), epigenetic alteration (Baccarelli et al, 2008;Salam et al, 2012;Byun et al, 2013;Hou et al, 2013) infant mortality (Woodruff et al, 1997;Lipfert et al, 2000;Dales et al, 2004;Glinianaia et al, 2004) atherosclerosis (Araujo et al, 2008;Araujo, 2011;Kaufman, 2011), stroke (Brook, 2008;Brook andRajagopalan, 2009, 2012;Maheswaran et al, 2010Maheswaran et al, , 2012, rheumatic autoimmune disease (Zeft et Table 1. Particulate matter and health outcomes for PM 10 , PM 2.5 and ultrafine particles (UFPs).…”
Section: Introductionmentioning
confidence: 99%